2018
DOI: 10.1007/s10230-018-0547-8
|View full text |Cite|
|
Sign up to set email alerts
|

An Overview of Priority Pollutants in Selected Coal Mine Discharges in Europe

Abstract: Coal mine water discharges in several European countries were investigated as part of the European Commission's MANAGER project. The emphasis of the project was identification of priority pollutants and potential remedial approaches. The main identified priority pollutants were sulphate (all countries) and iron (all countries except Greece). High concentrations of chloride (particularly in Germany and Poland) were associated with discharge of saline mine waters linked to the presence of fossil sea water; these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Some of the most critical and widespread mining impacts are related to the pollution of soil and the aquatic environment by metals and metalloids, due to the severity of the negative effects on ecosystems and on human health [4][5][6]. The environmental degradation resulting from the leaching of Potentially Toxic Elements (PTEs) and compounds, such as Polycyclic Aromatic Hydrocarbons (PAHs) from mine waste piles, as well as from acid mine drainage, is considered a major concern by governmental agencies, mining companies, and citizens [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the most critical and widespread mining impacts are related to the pollution of soil and the aquatic environment by metals and metalloids, due to the severity of the negative effects on ecosystems and on human health [4][5][6]. The environmental degradation resulting from the leaching of Potentially Toxic Elements (PTEs) and compounds, such as Polycyclic Aromatic Hydrocarbons (PAHs) from mine waste piles, as well as from acid mine drainage, is considered a major concern by governmental agencies, mining companies, and citizens [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, due to the past and ongoing mine water pumping activates in the Ruhr region, water table levels in the subsurface have been significantly reduced. Currently average water table level in coal mines amounts to approximately 600 m (Brücker and Preuße 2020;Gombert et al 2018), where in some cases water levels reduced to 1200 m were observed. Such significant differences in mine water table levels will cause pore pressure disturbances and, as a result, reactivation potentials change.…”
Section: In Situ Stress Statementioning
confidence: 99%
“…To provide a safe working zone this flooding/inrush require dewatering. For example, the hard coal area of Ruhr (Germany) requires a pumping rate of 48e54 Mm 3 /a, which is significantly higher than the normal flow rate of <5 m 3 /h [57].…”
Section: Backfill and Dewatering: Causes Of Floodingmentioning
confidence: 99%
“…This rebound is either the rise in groundwater due to cessation of pumping activities also known as passive (internal flooding) or active flooding (external flooding) in which water inrush takes place [113]. In case of France, where half of coal basins are flooded, mine water of these French mines drain into surface water bodies including rivers (95%), lakes (4%) and sea water (1%) [57]. If we take an example of China, water inrush incidents can be divided into four major categories i.e.…”
Section: Backfill and Dewatering: Causes Of Floodingmentioning
confidence: 99%